Pot Tanaman Sebagai Media Komunikasi Visual Kampanye Edukasi Manfaat Tanaman Kumis Kucing Bagi Usia 17-25 Tahun Di Kota Palembang - Febriansyah, Luki; Yulius, Yosef; Halim, Bobby (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
ABSTRACTTraditional medicine is a combination of science, belief and community tradition which aims tomaintain health, namely the Cat's Whisker plant. The leaves of the cat's whisker plant containactive compounds such as flavonoids, saponins and tannins. However, currently the Cat'sWhisker Plant is not being introduced to the public, especially teenagers, in the introduction ofthe Cat's Whisker plant, there are not many campaigns and promotions and there is no existingpromotional media related to the introduction of the Cat's Whisker plant. It is hoped that thisdesign can attract the interest of the people in Palembang City, especially teenagers, byintroducing and educating the cat's Whisker plant, designed through plant pots with interestingillustrations and interactives that can teach how to consume and process the cat's Whiskerplant. The works created are categorized into three media, namely the main media, plant pots,issue media including posters, banners, motion graphics and supporting media including tshirts, tumblers, tote bags, mascots, packaging.Keywords : Campaign, Plants, Cat's Whiskers, Teenagers, Palembang.